The Results of the Research of Biological and Genetic Properties of the Anthrax Strains Isolates during the Epizootic 2016 in Yamal-Nenets Autonomous District - D. L. Pavlov; N. V. Onuchina; A. V. Kuznetsovskiy; O. O. Fomenkov; A. S. Tumanov (Вестник войск РХБ защиты)
The article is dedicated to the results of the studies of Bacillus anthracis isolates, selected during the liquidation of anthrax epizootic in the Yamal-Nenets Autonomous District in summer 2016. The above mentioned isolates turned out to be highly sensitive to the means of general emergency prophylaxis (doxycycline, pefloxacin and rifampicin), as well as to the main means of special emergency prophylaxis and etiotropic therapy of anthrax (ampicillin, ciprofloxacin, amikacin, gentamicin). The studies revealed also the high virulence of B. anthracis strain in white mice. The lethal dose (LD50) turned out to be from 5 to 7 spores, and the average lifetime of animals since the moment of contamination till death did not exceed 3,6 days. The results of VNTR typing allowed to state, that the genotype of B. anthracis isolates, that caused the anthrax epizootic outbreak in the Yamal, was not exotic for Russia. The Russian National Collection of Microorganisms already possesses the stem with identical VNTR-genotype. The Yamal isolates of B. anthracis coincide with the B. anthracis strain 1051, obtained in 1935 by the veterinary laboratory in Ufa from the corpse of the horse. It shows the presence of steady hotbeds of B. anthracis of the above mentioned genotype in our country's soil in the Southern Urals.